THE SIGNIFICANCE OF DETERMINING THE TAX BURDEN IN A CROSS SECTION (Marketing Journal, 2025)
The article examines the methodology for determining sectoral tax burden, its theoretical and practical foundations, as well as international experiences. It outlines the procedure for using indicators such as gross revenue, net profit, profit before tax, and value added when calculating the tax burden. The study also highlights the economic importance of assessing tax burden across sectors, its role in optimizing tax policy, and its impact on the investment climate.
Keywords: tax burden; gross revenue; net profit; value added; budget revenues; sectoral analysis; tax policy